Hydrostatic Injury Surgical Planning. Issue 2 (April 2015) - Wyatt, Sabrina N.; Lockhart, Mark E.; Richter, Holly E.
<x xml:space="preserve">Abstract</x> Abstract A multidisciplinary approach, including imaging, to evaluate and manage hydrostatic pelvic floor injuries is recommended.